КАК ПРОЧИТАТЬ ФОТОГРАФИЮ — АНАЛИЗ СТИХОТВОРЕНИЯ МЫ ЖИЛИ В ГОРОДЕ… (A PHOTOGRAPH) ИОСИФА БРОДСКОГО - Madloch, Joanna (Przegląd Rusycystyczny, 2020)
The goal of this article is to present relation between photography and Joseph Brodsky’s poetry on the example of the poem Мы жили в городе ...., which was translated into English by the poet and titled A Photograph. In the first part the author analyses the structure of the presented world in context of his stylization on a photograph. While putting stress on Brodsky’s “photographic seeing” the author pays attention to lighting, colors, geometry and fragmentary nature of the presented world. The results of bringing the meanings of the visual work of art upon the literary work are examined in the second part of the article. The author points on such qualities of a photo-text as: disruption of the temporal-spatial structure of the presented world which is a consequence of a priori elegiac nature of photography; questioning the fictional character of the poem and introducing metonymic meanings on the place of metaphorical ones (as a result of the documentary character of photography); bringing in, implied by photography, notions associated with passing, death and immortality